دلالاتُ لفظي الإكمالِ والإِتمامِ في كتابِ ربِّ الأَنام - روستم, م.ی. هوز عمر; محمد, م.ی. سوران علي (Sulaimani Journal for Humanities, 2023)
This study aims to show the semantic differences between the two consepts (completion) and (finishing) and their place of use and contexts in the views of linguists, interpreters of the holy Qur'an and hadith scholars in ancient and modern times, in purpose of correcting of using writing and speaking styles among students, writers, experts.